PERILAKU LENTUR BALOK-L BETON BERTULANG BERLUBANG DITINJAU SECARA EKSPERIMEN DAN ANALISIS NUMERIK MEMAKAI SOFTWARE GID-ATENA - Kori Effendi, Mahmud (Jurnal Teknik Sipil dan Perencanaan, 2010)
Abstract:.Investigation on behavior of openings-beam reinforced concrete with the variation type of sidedÃÂ  is ÃÂ conductedÃÂ  experimentallyÃÂ  andÃÂ  numericalÃÂ  analyticallyÃÂ  usingÃÂ  GID-ATENAÃÂ  software.ÃÂ  Used specimensÃÂ  wereÃÂ  reinforcedÃÂ  concreteÃÂ  L-shapedÃÂ  beamÃÂ  designedÃÂ  withÃÂ  ultimateÃÂ  loadÃÂ  2600ÃÂ  NÃÂ  and having tension reinforcement 2D13 with roll and hinge support. Beam had 2 m span, 150 mm web width, 250 mm high, effective 317 mm width and slab 100 mmÃÂ  thick,. To differentiate behavior of openings, a specimen without openings ( BLK01), a specimen with openings 100 mm x 100 mm ( BLKLB01), a specimen with openings 200 mm x 100 mm ( BLKLB02) were made. An opening was 150 mmÃÂ  fromÃÂ  right support. Pure moment was done withÃÂ  load 650 mmÃÂ  from support. To compare experiment,ÃÂ  3DÃÂ  modelÃÂ  GID-ATENAÃÂ  wasÃÂ  analyzed.ÃÂ  TheÃÂ  materialÃÂ  modelÃÂ  ofÃÂ  concreteÃÂ  was CCCOMBINEDMATERIALÃÂ  andÃÂ  CC1DELASTLSOTROPICÃÂ  forÃÂ  reinforcement.ÃÂ  ThisÃÂ  analysisÃÂ  used geometricÃÂ  and materialÃÂ  nonÃÂ  linearÃÂ  analyses.ResultÃÂ  of GID-ATENAÃÂ  analysisÃÂ  indicateÃÂ  thatÃÂ  theÃÂ  first crack load were less than 42-62 %, ultimate load were less than 33-47%, mid-span displacement at first crack load were less than 55-86%, and mid-span displacement at ultimate load were less than 45-70% comparedÃÂ  toÃÂ  the experimentÃÂ  result. First crack pattern of BLK01 occuredÃÂ  inÃÂ  the mid-span whileÃÂ  BLKLB01ÃÂ  andÃÂ  BLKLB02ÃÂ  occurredÃÂ  belowÃÂ  theÃÂ  hole. ResultÃÂ  ofÃÂ  analysis GID-ATENAÃÂ  getÃÂ  the different result of its first crack pattern. Keywords: openings-beam, L-shaped beam, GID-ATENA ÃÂ  Abstrak:ÃÂ  PengamatanÃÂ  perilakuÃÂ  balokÃÂ  betonÃÂ  bertulangÃÂ  berlubangÃÂ  diÃÂ  badanÃÂ  denganÃÂ  variasiÃÂ  entuk persegi panjangÃÂ ÃÂ  dilakukanÃÂ  secara eksperimen. BendaÃÂ  ujiÃÂ  yang digunakan adalahÃÂ  balokÃÂ  LÃÂ  beton bertulangÃÂ  yangÃÂ  dirancangÃÂ  denganÃÂ  bebanÃÂ  2600ÃÂ  NÃÂ  danÃÂ  menghasilkanÃÂ  tulanganÃÂ  tunggalÃÂ  2D13 denganÃÂ  tumpuan sendi danÃÂ  rol. Balok mempunyai bentang 2 m,ÃÂ  lebar web 150 mm,ÃÂ  tinggi 250 mm, tebal slab 100 mm, lebar efektif 317 mm. Untuk mengetahui perilaku lubang di badan maka dibuatÃÂ  bendaÃÂ  ujiÃÂ  balok ÃÂ tanpaÃÂ  lubangÃÂ  (BLK01),ÃÂ  balokÃÂ  denganÃÂ  lubangÃÂ  100ÃÂ  mmÃÂ  xÃÂ  100ÃÂ  mm (BLKLB01),ÃÂ  balokÃÂ  denganÃÂ  lubangÃÂ  200 mmÃÂ  xÃÂ  100 mmÃÂ  (BLKLB02).ÃÂ  JarakÃÂ  lubangÃÂ  150 mmÃÂ  dari tumpuan kanan. Masing2 benda uji 1 buah. Untuk mengetahui kapasitas beban maksimum yang ditahanÃÂ  balok,ÃÂ  balokÃÂ  ditesÃÂ  lentur murniÃÂ  denganÃÂ  jarakÃÂ  bebanÃÂ  titikÃÂ  650 mmÃÂ  dariÃÂ  tumpuan.ÃÂ  Hasil analisis GID-ATENA menunjukkan bahwa beban retak balok pertama lebih kecil 42-62 %, beban ultimit balok lebih kecil 33-47%, lendutan tengah bentang pada beban retak pertama lebih kecil 55-86%,ÃÂ  danÃÂ  lendutanÃÂ  tengahÃÂ  bentangÃÂ  padaÃÂ  bebanÃÂ  ultimitÃÂ  lebihÃÂ  kecilÃÂ  45-70%ÃÂ  terhadapÃÂ  hasil eksperimen. Pola retak pertama balok BLK01 terjadi di tengah bentang sedangkan BLKLB01 dan BLKLB02ÃÂ  terjadi di bawahÃÂ  lubang. Hasil analisis GID-ATENA mendapatkan hasil yang berbeda pola retak pertamanya. Kata Kunci: Balok lubang, Balok L, GID-ATENA